THE INFLUENCE OF PRODUCT QUALITY, PROMOTION, BRAND IMAGE AND BRAND TRUST ON PURCHASING DECISIONS PURCHASE OF AQUA MINERAL WATER FOR MALIKUSSALEH UNIVERSITY STUDENTS - Mita Darmayanti; Rahmaniar; Maryudi; Heriyana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Abstract this research aims to test of product quality, promotion, brand image and brand trust on purchase decision. The data in this research was collected using questionnaires as the data collection instrument. The sample consisted of 130 respondents. This research used a quantitative approach with multiple linear regression analysis and was processed using SPSS (Statistical Package for the Social Sciences). The hypothesis was tested using SPSS version 25.0. The results of this study indicate that, partially, the product variable has a positive and significant effect on purchase decision of Aqua products,statistically 0.000 < 0.05, and has a t-value > t-table value of 4.713 > 1.657. The promotion variable does not affect and is not significant for purchase decision of Aqua products, statistically 0.947 > 0.05, and has a t-value < t-table value of 0.066 < 1.657. Meanwhile, the brand image variable has a positive and significant effect on purchase decision of Aqua products, statistically 0.002 < 0.05, and has a t-value > t-table value of 3.246 > 1.657. Additionally, the product brand trust has a positive and significant effect on purchase decision of Aqua products, statistically 0.004 < 0.05, and has a t-value > t-table value of 2.974> 1.657. The Adjusted R Square value of the independent variables, namely product quality, promotion, brand image and brand trust, shows that 41.2% of the variance is explained by these variables, while the remaining 58.8% is explained by other variables not included in this study.